The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.ejor.2020.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Front-office multitasking between service encounters and back-office tasks

Abstract: We model the work of a front-line service worker as a queueing system. The server interacts with customers in a multi-stage process with random durations. Some stages require an interaction between server and customer, while other stages are performed by the customer as a self-service task or with the help of another resource. Random arrivals by customers at the beginning and during an encounter create random lengths of idle time in the work of the server (breaks and interludes respectively). The server consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…A related set of papers on multitasking are queuing models with one server or group of servers balancing two work queues (Gans andZhou 2003, Legros et al 2020). Legros et al (2020) discuss service operators' switching between customer interaction and back-office tasks. They derive optimal threshold policies for using the interlude time between customer interactions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A related set of papers on multitasking are queuing models with one server or group of servers balancing two work queues (Gans andZhou 2003, Legros et al 2020). Legros et al (2020) discuss service operators' switching between customer interaction and back-office tasks. They derive optimal threshold policies for using the interlude time between customer interactions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although much emphasis is placed on the primary tasks to be completed, such as patient treatment or surgery (Bartel et al 2020, Youn et al 2022, assembling a car in a factory (Bernstein & Kok 2009), or answering a call in a call center (Aksin et al 2007), operations also include secondary tasks that support the primary work (Dai et al 2015, Legros et al 2020. These might consist of EHR use, hand hygiene (Dai et al 2015) or lab tests in healthcare (Batt and Terwiesch 2017), supply positioning or tool preparation in manufacturing, or data entry in call centers.…”
Section: Introductionmentioning
confidence: 99%
“…This also makes a difference with our context, where urgent customers can interrupt the treatment of some back-office tasks. In a context with switching time allocation between urgent and nonurgent tasks, Legros et al (2020) showed that idling in the presence of waiting customers may be optimal to avoid too many switches. Further references on queue-blending operations include Keblis and Chen (2006); Pichitlamken et al (2003); Pang and Perry (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although nonoptimal, this policy has the advantage of not letting the agent leave any customers waiting in the queue since this would not be appreciated in visible systems. It also reduces the frequency of switches between idle and busy states for the agent (Legros et al, 2020). The stationary probabilities are computed via a two‐dimensional Markov chain analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the agent reservation policy can be implemented, that is, when the number of agents reserved for the inbound calls reaches a threshold, an agent can make an outbound call or respond to an email request. We refer the interested reader for further reading on call blending to Deslauriers et al (2007), Pang and Perry (2014), Legros et al (2015Legros et al ( , 2020.…”
Section: Introductionmentioning
confidence: 99%